THÔNG BÁO KHOA HỌC XÂY DỰNG HỆ THỐNG CHUẨN CHUNG CỦA CƠ SỞ DỮ LIỆU ĐỊA VẬT LÝ KHU VỰC TRONG CÁC ĐƠN VỊ THUỘC BỘ TÀI NGUYÊN VÀ MÔI TRƯỜNG - Khánh, Chu Quốc; Giàu, Lại Mạnh; Tuấn, Phan Minh; Hải, Lê Thanh; Hậu, Đặng Văn; Mạnh, Phùng Đức (Vietnam Journal of Earth Sciences, 2011)
The criterion system of regional geophysical database in the Ministry of Natural Resources and Environment The archive regional geophysical database at present has many disadvantages. This paper determines a criterion system of regional geophysical database, involving: structure of database, structure of archived database system, format of database, format of document, as well as content of document, .etc. At the same time, six programs have been established for regional geophysical database archiving. Based on the available regional geophysical database, the authors have proposed principles and methods of standardization for archiving regional geophysical database. The method includes main contents: Standardization of directory and directory system; Standardization of data file format; Standardization of information content of archive geophysical data files; Standardization of information content of archive mapping files. The authors present some examples about block scheme of archiving geophysical database, of database structure of every aerogeophysical report, and of database structure of aeromagnetic national map as a basic for compiling database and constructing administrative programs.